2016
DOI: 10.1080/00140139.2016.1199816
|View full text |Cite
|
Sign up to set email alerts
|

A long-term evaluation of the stage of change approach and compensable injury outcomes – a cluster-randomised trial

Abstract: This study investigated the long-term injury outcomes for workers in companies from a range of industries which had been randomly allocated to receive ergonomics interventions tailored according to the stage of change (SOC) approach or standard ergonomics advice. Differences in compensable injury outcomes between the groups were analysed using logistic regression models. Questionnaire results from face-to-face interviews to assess musculoskeletal pain and discomfort (MSPD), job satisfaction and other factors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…While not explicit in our survey, it is likely that perceptions of wage unfairness and working hours may be associated with low levels of job satisfaction. Previous studies have reported that those who were dissatisfied with their work were almost three times more likely to report pain and four times more likely to experience an injury [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…While not explicit in our survey, it is likely that perceptions of wage unfairness and working hours may be associated with low levels of job satisfaction. Previous studies have reported that those who were dissatisfied with their work were almost three times more likely to report pain and four times more likely to experience an injury [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that tailored interventions were significantly more effective in changing behaviour and reducing musculoskeletal disorders in a diverse range of workplace settings Haslam 2006, 2007). Rothmore et al (2017) investigated compensable injuries among workers who had received ergonomics advice tailored to stage of change compared to standard ergonomics advice. They demonstrated that those given tailored advice were less likely to report a compensable injury than those given standard advice.…”
Section: Introductionmentioning
confidence: 99%